2021
DOI: 10.1038/s41584-021-00603-4
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic diseases in Africa

Abstract: Historically, rheumatic diseases have not received much attention in Africa, particularly in sub-Saharan Africa, possibly owing to a focus on the overwhelming incidence of infectious diseases and the decreased life span of the general population in this region. Global attention and support, together with better health policies and planning, have improved outcomes for many infectious diseases; thus, increasing attention is being turned to chronic non-communicable diseases. Rheumatic diseases were previously con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 105 publications
0
26
0
2
Order By: Relevance
“…Limited drug availability and poverty likely contribute to high rates of corticosteroid and nonsteroidal anti‐inflammatory use even though steroids pose a greater risk of side effects ( 17 , 29 , 30 ). Demand for MTX in Africa will likely increase with greater awareness of chronic rheumatic diseases, optimization of their treatment approaches, and growing number of specialty‐trained rheumatologists ( 31 ). Solutions to address MTX access will vary by region and will likely require multifaceted approaches engaging national and regional governments to stabilize supply pathways and enhance safe drug dispensing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Limited drug availability and poverty likely contribute to high rates of corticosteroid and nonsteroidal anti‐inflammatory use even though steroids pose a greater risk of side effects ( 17 , 29 , 30 ). Demand for MTX in Africa will likely increase with greater awareness of chronic rheumatic diseases, optimization of their treatment approaches, and growing number of specialty‐trained rheumatologists ( 31 ). Solutions to address MTX access will vary by region and will likely require multifaceted approaches engaging national and regional governments to stabilize supply pathways and enhance safe drug dispensing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,9 There is a lack of data in Africa on the prevalence of RA. [10][11][12] Data extracted from a systematic analysis of 9 (out of 10 included) studies in sub-Saharan Africa and published from 1968 to 1988 estimated a crude prevalence of 0.36% for RA. 11 A systematic review and meta-analysis of populationbased studies from 11 African countries -urban and rural settings -estimated different crude prevalence.…”
Section: Impact Statementmentioning
confidence: 99%
“…[1] A possible explanation for this is the age limitation for participation in the study, which was 18 to 50 years, and in addition, African samples have reported an average age of onset of 27 years. [11] The large distribution of participants located in the Gauteng province is attributed to Gauteng having the greatest population density, coupled with the highest internet connectivity in South Africa. [12] Global Physical Activity Questionnaire (GPAQ)…”
Section: Demographicsmentioning
confidence: 99%